MUSIC PUBLISHERS' CATALOGS. (Notes, 2006)
Presents a list of music publishers' catalogs compiled by the periodical "Notes," including those of the Associated Board of the Royal Schools of Music, Finnish Music Information Centre and Masters Music Publications.